THE INFLUENCE OF HEDONIC VALUE AND UTILITARIAN VALUE ON PURCHASING DECISIONS FOR SAMSUNG SMARTPHONES - Santoso, Anugrah Bayu; Wardhani, Nuruni Ika Kusuma (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
In the modern era, technological advances are the main factor driving changes in various aspects of human life. The rapid development of technology today allows people to access information easily through various media, such as using smartphones so that it becomes a human need, especially among students. This makes smartphone companies compete and innovate to capture market share. This study aims to determine the effect of Hedonic value and Utilitarian value variables on purchasing decisions for Samsung smartphones The approach used in this research is quantitative. The study population consisted of university students in Surabaya City, with a sample of 90 respondents. The sampling method used non-probability sampling technique through purposive sampling. Data were collected using a questionnaire distributed via Google Form, and data analysis was carried out using the Structural Equation Modeling (SEM) method using the Partial Least Squares (PLS) analysis tool and is carried out through a two-stage approach with the help of SmartPLS. The results showed that Hedonic Value and Utilitarian Value have a positive and significant effect on Samsung Smartphone Purchasing Decisions.